CFS: An effective statistical texture descriptor - Alireza Akoushideh (Institute of Advanced Engineering and Science, 2020)
Coarseness is an effective description for texture analysis and many approaches capture this property of texture in different methods. In this research, we propose a new texture descriptor (CFS) that works based on coarseness and the fineness similarity score. For tuning of its configuration, we collect coarse and fine textures based on human visual perception at first. After that, we relabel the